The Fast Red Road - Jones, Stephen Graham (Florida normal Tallahassee, 1972)
The Fast Red Road, F Plainsong is a novel which plunders, in a gleeful, two-fisted fashion, the myth and pop-culture surrounding the American Indian. It is a story fueled on pot fumes and blues, borrowing and distorting the rigid conventions of the traditional Western. Indians, cowboys, and outlaws are as interchangeable as their outfits; men strike poses from Gunsmoke, and horses are traded for Trans-Arms. Pidgin, the half blood protagonist, inhabits a world of illusion of aliens, ghosts, telekinesis, and water pistol violence, where television offers redemption, and the Indian always gets it up the ass.
Keywords: Fiction